On the Connexion between Scotland and the Council of Constance in the Fifteenth Century (Proceedings of the Society of Antiquaries of Scotland, 1862)
This article discusses how the decisions of the Council of Constance, 1414-1418, were received by the Scottish religious authorities. The author describes how the declaration of this Council on the subject of who was the true Pope triggered a heated debate among the Scottish clergy. It is also noted that members of the Scottish church were broadly in favour of the treatment of Huss and Jerome (see pp.408-424), and even emulated this example on a heretical preacher in St Andrews in 1433.